PENDAMPINGAN PEMBUATAN MIE DAN BISKUIT DARI TEPUNG SAYURAN PADA KELOMPOK IBU-IBU PETANI DI DESA SINDON NGEMPLAK BOYOLALI - Rusdin Rauf; - Muhtadi; Kun Harismah; - Saifuddin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The development of a variety of products processed from starchy vegetables needed to be trained and applied for the farmers of vegetables to help cope with the price of vegetables was very cheap and increased its economic value. This activity aimed to develop products processed from starchy vegetables in the village of Sindon-Ngemplak-Boyolali, which was expected to increase economicvalue, both in terms of revenues, new business development and the welfare of farmers. The partner of community development activities were ibu-ibu  PKK ,  pengajian Aisyah  and kelompok wanita tani (KWT) "Mawar" in the Sindon village. The method was used in this activity included the application of science and technology on the manufacture of starchy vegetables, assisting the production of a variety of processed starchy vegetables namely wet noodles, instant noodles, and biscuits were made fromvegetable starch. Results and implications that have been obtained from this activity all women group partners have been able to master the skills to cultivate vegetable flour into wet noodle products, instant noodles and biscuits. However, the constraints and problems still exist  was the ability to develop the marketing of starchy vegetables products from the group of women partners is still verylow.Keywords  :  Products processed starchy vegetables, wet and instant noodles, biscuit, the group of  women partners Sindon Village